2019
DOI: 10.23960/jat.v7i2.3367
|View full text |Cite
|
Sign up to set email alerts
|

Aplikasi Sabut Kelapa Dan Pupuk Bokasi Kotoran Ayam Terhadap Pertumbuhan Bibit Sawit Di Pre Nurseri

Abstract: Penggunaan bibit kelapa sawit yang bermutu akan menentukan keberhasilan jangka panjang pengelolaan perkebunan kelapa sawit. Salah satu faktor yang menentukan keberhasilan pembibitan kelapa sawit di tingkat prenursery adalah ketersediaan air yang cukup. Bila terjadi kekurangan air dapat mengakibatkan penyimpangan pertumbuhan dan menghasilkan bibit yang tidak prima. Penelitian ini bertujuan untuk melihat kemampuan sabut kelapayang dikombinasikan dengan pupuk bokasi kotoran ayam untuk menahan air di dalam polibag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Liquid Organic Fertilizer to encourages oil palm growth in pre-nursery (Anhar et al, 2021). Effendy et al (2019) also stated that treating chicken manure with as much as 200 g/polybag significantly affected prenursery seedlings growth of oil palm. The organic material using in the pre nursery, like cow manure as much as 360 g/polybag + NPK 4.5 g/polybag could increase the growth of seedlings with the content of organic C, total N, and C/N ratio of 40.94%, 2.33%, and 17.60, respectively (Adileksana et al, 2020).…”
Section: Article Historymentioning
confidence: 99%
See 1 more Smart Citation
“…Liquid Organic Fertilizer to encourages oil palm growth in pre-nursery (Anhar et al, 2021). Effendy et al (2019) also stated that treating chicken manure with as much as 200 g/polybag significantly affected prenursery seedlings growth of oil palm. The organic material using in the pre nursery, like cow manure as much as 360 g/polybag + NPK 4.5 g/polybag could increase the growth of seedlings with the content of organic C, total N, and C/N ratio of 40.94%, 2.33%, and 17.60, respectively (Adileksana et al, 2020).…”
Section: Article Historymentioning
confidence: 99%
“…Manure with the highest seedling height was produced by applying 50 g/polybag chicken manure (Table 5). The research results by Effendy et al (2019) reported that the application of 200 g/polybag chicken manure affected the growth of oil palm seedlings on ultisol growing media.…”
Section: The Effect Of Lof and Manure On Ultisolmentioning
confidence: 99%
“…Peningkatan jumlah penumpukan sampah yang semakin tahun semakin banyak merupakan cerminan bahwa permasalahan sampah membutuhkan sebuah penanganan yang tepat. Agar mampu menjawab masalah persampahan di Indonesia, maka sebaiknya menciptakan sistem pengelolaan sampah yang optimal dan solutif (Effendy et al, 2019). Akan tetapi, banyak dari masyarakat yang memiliki pola pikir bahwa pengelolaan sampah hanya melalui pendekatan kumpul-angkut-buang (on of pipe) dengan hanya mengandalkan keberadaan Tempat Pembuangan Akhir (TPA), sehingga masih ada kesulitan dalam mencapai sistem pengelolaan persampahan yang tepat dan optimal padahal jika dibiarkan begitu saja, sampah yang ada di TPA akan mengalami penumpukan dan persediaan lahan untuk TPA akan semakin berkurang (Lukiana et al, 2021).…”
Section: Analisis Situasiunclassified
“…In addition to providing nutrients for plants, fertilizer application can also help improve soil physical and chemical properties, and increase nutrient levels in the soil (Effendy & Jalal, 2019;Warsito et al, 2017). Fertilizer application also affects the development of microbes in the soil that are associated with roots.…”
Section: Literature Reviewmentioning
confidence: 99%